2014
DOI: 10.1016/j.mce.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the reproductive cycle and early pregnancy by relaxin family peptides

Abstract: a b s t r a c tThe relaxin family of peptide hormones are structurally closely related to one another sharing a heterodimeric A-B structure, like that of insulin. They may also be active as unprocessed B-C-A pro-forms. Relaxin has been shown to pay a key role within the ovary, being involved in follicle growth, and ovulation. Relaxin is produced in large amounts also by the corpus luteum where it acts as an endocrine hormone positively affecting implantation, placentation and vascularization during the all-imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 104 publications
0
20
0
2
Order By: Relevance
“…RXFP1 is expressed in sperm in both mice (Krajnc-Franken et al, 2004) and humans (Carrell et al, 1995;Ferlin et al, 2012) and increases sperm motility and facilitates penetration into oocytes (Weiss, 1989). Another potential role for seminal relaxin may be to act on the female reproductive tract to prepare the endometrium for implantation (Telgmann and Gellersen, 1998;Unemori et al, 1999;Anand-Ivell and Ivell, 2014).…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 99%
“…RXFP1 is expressed in sperm in both mice (Krajnc-Franken et al, 2004) and humans (Carrell et al, 1995;Ferlin et al, 2012) and increases sperm motility and facilitates penetration into oocytes (Weiss, 1989). Another potential role for seminal relaxin may be to act on the female reproductive tract to prepare the endometrium for implantation (Telgmann and Gellersen, 1998;Unemori et al, 1999;Anand-Ivell and Ivell, 2014).…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 99%
“…In females INSL3 is found at lower levels than in males, but it is detectable in serum and is largely produced in the theca interna cells of ovarian antral follicles in humans 8 . The role of ovarian INSL3 in humans is currently unknown however animal studies have demonstrated putative roles for thecal derived INSL3 in germ cell survival 9 and follicular androgen production 10 . In addition to its reproductive roles, INSL3 has been implicated in bone metabolism in males where low levels are associated with an increased risk of osteopenia and osteoporosis 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Lgr-related genes are also present in humans and include those encoding relaxin-family peptide receptors RXFP1 and RXFP2, which among other functions are necessary for normal reproduction in both sexes (reviewed in ref. 23).…”
mentioning
confidence: 99%